(untitled) (Journal of Guidance and Counselling Studies, 2025)
This paper focuses on parenting styles and family communication pattern as predictors of secondary school students’ academic achievement in English language in Enugu state, Nigeria. Three research questions guided the study. Three null hypotheses were tested for study. Correlation survey research design was adopted for this study. The population for this study comprised 24456 senior secondary school two (SS II) students from over 300 secondary schools situated in the six education zones in Enugu state. The sample for this study comprised 2448 SS II secondary school students drawn from the six education zones in the state. The instruments adopted for data collection are: Parenting Style Inventory (PSI), Communication Pattern Questionnaire (CPQ) and Students Academic Achievement Scores in English language. In 1991, Buri developed parental authority questionnaire (PAQ) to assess Baumrind’s (1966) permissive, authoritarian, and authoritative parenting styles consisting of 30 Likert type items. The test provides 30 items for each parent, and the children need to respond on a 5-point response options of Never to Always 1 - 6. The communication pattern questionnaire (CPQ) is developed by Christensen and Sullaway (1984). The questionnaire adopted for this study are standard questionnaires which have been adopted for use in Nigeria by other scholars and researchers to conduct studies in related study areas. The reliability of the scale was established by test-retest method after an interval of one week. The test-retest coefficient of reliability of responsiveness variable in the scale is 0.81 and for control it is 0.83. The index of validity and index of reliability indicate that the scale has validity and reliability for measuring the parenting style of higher secondary school students (Gafoor and Kurukkan, 2014). The communication pattern questionnaire (CPQ) is developed by Christensen and Sullaway (1984). The reliability of this scale has been established and confirmed by many researchers. The average value of Cronbach alpha was 0.79 for conformity and 0.89 for conversation. In the same vein, Jokwar and Rahimi cited in Geetika (2019) had reported reliability of this scale for the dialogue orientation 0.93 and 0.88 for conformity orientation by using Cronbach alpha. The administration of the instrument was done through direct delivery approach. The research questions 1 to 2 was answered using linear regression analysis while research questions 3 with the null hypotheses was analyzed using multiple regression analysis. The findings of the study revealed that This indicates that authoritative parenting style had contributed to 62.5 percent for the student’s academic achievements in English language. authoritative parenting style is a significant predictor of the secondary school student’s academic achievements in English language in Enugu State. This indicates that authoritarian parenting style had contributed to 34.5 percent for the student’s academic achievements in English language. authoritarian parenting style is a significant predictor of the student’s academic achievements in English language in Enugu State. Permissive parenting style had contributed to 3.8 percent for the student’s academic achievements in English language. Permissive parenting style is a significant predictor of the student’s academic achievements in English language in Enugu State. Conversation communication pattern had contributed to 12.9 percent for the student’s academic achievements in English language. Conversation communication pattern is a significant predictor of the secondary school student’s academic achievements in English language in Enugu State. Conformity communication pattern had contributed to 4.6 percent for the student’s academic achievements in English language. conformity communication pattern is a significant predictor of the secondary school student’s academic achievements in English language in Enugu State. parenting styles and communication patterns had contributed to 54.1 percent on the student’s academic achievements in English language in Enugu State. Parenting styles and communication patterns of secondary school students are significant predictors of their academic achievements in English language. Conclusions were drawn and recommendations made accordingly.